Design SPO2 and BPM Monitoring System To Monitor The Patient's Health Using Anroid: SPO2 and BPM Monitoring System - Desak Ketut Sutiari; Laode Sahlan Zulfadlih; Muhammad Sainal Abidin; Wayan Somayasa; Rudi Kizhara (STIKes Mandala Waluya Kendari, 2023)
Background: Many efforts have been continuously developed in order to avoid contacting with the Covid-19 viruses and other infectious diseases during the pandemic. For people infected with Covid-19, monitoring their oxygen saturation and heart rate at all times is very important. Beside that the chance of being exposed by the viruses from the patient is very high. In this study, a device that can monitor SpO2 in the blood and heart rate using the Blynk application is designed. Health workers can control patients using an android that has the Blynk application installed.The measurement patient results can be monitored with the LCD manually and remotely via Android. Android-based measurements can reduce the risk of health workers making direct contact with the virus and the patient of covid-19. The information can be monitored in real time.. Methods: This system is designed using a wifi-based Esp8266 Wemos D1 mini module as the input and output controller. The detection of the oxygen levels as well asthe BPM is conducted by using Max30100 censor Results: The studies show that the measurement results performed on the LCD can be read on an Android using the Blynk application. Data transmission that comes from several devices can be monitored in one android. The results show that the measurement data on the LCD are the same as those performed using the Blynk application Conclusion: The results shown that the measurement error level resulted by the SPO2 as well as the BPM is detected to the value of 0.021% and 0.012%, respectively. Beside that this developed device is also shown to be portable, effective, safe and easy to use.